Desing and implementation of the Poka Yoke tool for cost optimization in the sports footwear sector - Anampa Gómez, Alejandra Anastacia; Quispe Gaspar, Adriana Rosario; Polo Herrera, Kelly Milena; Díaz Díaz, Marco Antonio (LACCEI, 2025)
This study addresses the high defect rate in the screen-printing process within the Peruvian sports footwear manufacturing sector, which generates significant rework, operational inefficiencies, and increased costs. The root cause was identified as the lack of standardized procedures, leading to frequent misalignments and improper ink dosage during manual operations. To mitigate these issues, a Lean Manufacturing Poka Yoke system with an integrated verification sensor was designed and implemented. The device validates alignment and ink parameters before printing, allowing the process to continue only if conditions are correct, with visual and auditory alerts for errors. The implementation followed five phases: planning, design, training, execution, and evaluation. Results showed a reduction in defect rates from 1.13% to 0.50%, decreasing rework costs by approximately USD 1,921 annually. Economic indicators confirmed feasibility, with a NPV of USD 1,069.98, an IRR of 30%, and B/C ratio of 2.48. Beyond economic gains, the intervention improved operator confidence, process reliability, and workplace organization through continuous training and engagement. This research demonstrates that applying Poka Yoke in manual, error-prone processes within the footwear sector not only enhances product quality but also strengthens competitiveness, making it a viable strategy for other manufacturing environments facing similar challenges.